(untitled) (Texas Journal of Engineering and Technology, 2023)
A brief historical background and information about fire extinguishers at the present stage is given. Problematic issues are reflected. Innovative technical solutions and changes in the regulatory framework are considered. An analysis of the effectiveness of fire extinguishers is presented.